Cross-disciplinary advances in human computer interaction user modeling, social computing, and adaptive interfaces - Zaphiris, Panayiotis.; Ang, Chee Siang. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
It is becoming increasingly necessary to systematically take into account human interaction and activity, and new technologies along with the completely renewed social and cultural environments that such digital environments and interfaces are calling for are now capable of delivering. This book collects over 20 chapters covering the most recent in-depth issues within the field of human computer interaction (HCI). A necessary reference source for those in academia as well as the HCI industry, this book presents useful new approaches and methodologies for analysis, design, and evaluation.